A photofunctional platform of bis-terpyridine ruthenium complex-linked coordination polymers with structural diversity. Issue 47 (28th November 2022) - Wu, Aichun; Tang, Yuanlin; Li, Xinling; Zhang, Baohua; Zhou, Aiju; Qiao, Zhiwei; Tong, Lianpeng
Abstract : A family of novel coordination polymers (CPs) with topological diversity has been prepared based on a bis-terpyridine ruthenium linker. They provide a unique platform for the development of multifarious photofunctions. Abstract : Solvothermal syntheses of the bis(4′-carboxyl-2, 2′:6′, 2′′-terpyridine) ruthenium complex [Ru(tpyCOO − )2 ] as a linker and different metal anions as nodes constructed a family of ten novel coordination polymers (CPs) with different topological types, ranging from one-dimensional (1D) chains and two-dimensional (2D) networks to three-dimensional (3D) frameworks. The structural diversity of CPs is achieved by the various coordinating geometries of metal nodes, including 3d transition (monometallic or bimetallic), lanthanide, and group 4 (zirconium and hafnium) metal anions. The Ru complex linker plays the role of a light-harvesting unit and renders multifarious photofunctions to the CP materials. While the ytterbium CP (Yb–Ru ) exhibits near-infrared emission upon visible-light excitation, the 2D bimetallic Co/Ni CPs (Co x –Ni y –Ru ) and 3D interpenetrated copper CP (Cu–Ru ) show high to modest efficiencies toward the photocatalytic hydrogen evolution reaction. We suggest the series of new CPs with versatile structural traits as a unique platform for the research of photocatalysis and other photonic functional applications.